Transcriptomics-driven lipidomics (TDL) identifies the microbiome-regulated targets of ileal lipid metabolism. (December 2017) - Chakrabarti, Anirikh; Membrez, Mathieu; Morin-Rivron, Delphine; Siddharth, Jay; Chou, Chieh Jason; Henry, Hugues; Bruce, Stephen; Metairon, Sylviane; Raymond, Frederic; Betrisey, Bertrand; Loyer, Carole; Parkinson, Scott; et al.
Abstract The gut microbiome and lipid metabolism are both recognized as essential components in the maintenance of metabolic health. The mechanisms involved are multifactorial and (especially for microbiome) poorly defined. A strategic approach to investigate the complexity of the microbial influence on lipid metabolism would facilitate determination of relevant molecular mechanisms for microbiome-targeted therapeutics.E. coli is associated with obesity and metabolic syndrome and we used this association in conjunction with gnotobiotic models to investigate the impact ofE. coli on lipid metabolism. To address the complexities of the integration of the microbiome and lipid metabolism, we developed transcriptomics-driven lipidomics (TDL) to predict the impact ofE. coli colonization on lipid metabolism and established mediators of inflammation and insulin resistance including arachidonic acid metabolism, alterations in bile acids and dietary lipid absorption. A microbiome-related therapeutic approach targeting these mechanisms may therefore provide a therapeutic avenue supporting maintenance of metabolic health. Integrative Lipidomics: Microbiome regulation of lipid metabolism Microbes multifactorially impact host lipid metabolism bearing a significant impact in health and disease. A team led by Mojgan Masoodi and Scott Parkinson at Nestlé Institute of Health Sciences (NIHS) developed an integrative data driven approach for predictive lipidomics investigations of host-microbial impacts on lipid metabolism. Results ofin-vivo studies with germ-free mice inoculated withE. coli andin-vitro studies demonstrated the multifactorial nature of the impact ofE. coli on arachidonic acid metabolism in the ileum and altered host inflammation and lipid absorption. The findings provide insights into understanding the host-microbiome interactions and identifying microbiome-related solutions for maintaining health and tackling disease. The systems approach presented is applicable to investigate broad range of microbiome dependent and independent alterations in host lipid metabolism.